Implementation of legal regulations related to drug advertising in Serbia from the second half of the 19th to the first half of the 20th century - Arsić, Jasmina; Krajnović, Dušanka (Archives of Pharmacy, 2022)
The lack of regulations on drug advertising in the first half of the 19th century in Serbia enabled advertisers to make exaggerated, often false claims about the effect of advertised drugs, offering them as universal remedies for all diseases. Lack of information on the content of potentially dangerous substances, placebo effects and self-medication, were significant factors in their long-term popularity, but also criticism by health policy makers. The aim of this paper is to present the chronology of regulations in drug advertising in Serbia. Methods of documentation analysis and desk analysis of secondary data were used. The implementation of legal regulations on drug advertising first regulated the labeling of drugs. The Rulebook of the Permanent Expert Council for the Testing and Control of Medicines (1926) prohibited the sale of unregistered medicines, the advertising of existing medicines under other names and the advertising of strong drugs in the daily press. The Ordinance on the Advertising of Medicines and Medicinal Specialties in Daily Newspapers or in Other Manners (1931) determines the content of the text of an advertisement whose content was controlled by the Permanent Expert Council for Testing and Control of Medicines. The regulation of drug advertising in Serbia has evolved in the observed period, following the constant changes in the social, technological and political framework, while maintaining a high level of responsibility of policy makers and pharmacists in protecting the health of the population.